Detainees’ Perceptions of Procedural Justice: An Examination Throughout the Criminal Justice System - van Hall, Matthias (International journal of offender therapy and comparative criminology, 2024)
Procedural justice literature proposes that when individuals perceive their treatment by criminal justice authorities as more procedurally just, they will be more likely to view those authorities as legitimate and, in turn, show more compliant behavior. Knowledge on potential determinants of procedural justice is, therefore, crucial. Research suggests that prior perceptions of procedural justice may influence later judgements of procedural justice. The current study used data from the Prison Project, including information on detainees’ perceptions of their treatment by the police, the judge, the prison staff, the probation officer, and the lawyer. The findings show that detainees perceive the treatment by the lawyer as most procedurally just, while they evaluate the treatment by the police as least procedurally just. Further, how detainees experience the procedurally just treatment by the police is associated with how they feel treated by other authorities at a later stage in the criminal justice system.